Competency-based undergraduate curriculum implementation in anesthesiology-A survey-based comparison of two models of training - Rangraj Setlur; Nikahat Jahan; Nipun Gupta; Kiran Sheshadri (Wolters Kluwer Medknow Publications, 2021)
Background and Aim: Imparting the knowledge and skills of Anesthesiology to undergraduates can be challenging. Competency Based Undergraduate (CBUG) Curriculum for the Undergraduate medical students introduced by the Medical Council of India (MCI) aims to improve the quality of the Indian Medical Graduate (IMG). The Department of Anesthesiology and Critical Care of our college redrafted the training program and brought it in-line with the CBUG Curriculum beginning February 2019. A questionnaire based survey was conducted to assess the efficacy, satisfaction levels and the perception of the students towards the new competency based curriculum. The aim was to assess the students perception of the competency based curriculum and to evaluate two slightly different approaches to the implementation of the curriculum. Material and Methods: Two groups of undergraduate medical students belonging to the 6th and 8th term, underwent two different models of teaching. The 8th term students had already completed their theory classes based on the older curriculum a year ago when they were in 6th term. However, their clinics and tutorials were modelled as per the new CBUG Curriculum. The current 6th term students had their first exposure to Anesthesiology and their theory, tutorials and clinics were scheduled in the same term, simulation based training was added, the operation theatre rotation was held in the mornings at 0730hrs and the intensive care unit rounds were held in the evenings. There was no difference in the theory classes taken for the two batches, however the clinics were different. After both the batches finished their rotation, they were given the survey questionnaire to assess their perception of the model of CBUG Curriculum that they were exposed to. Results: The results of the survey revealed that about 80% of the students in both groups preferred that theory classes and practical training should be conducted in parallel in 6th term. About 60% students in both groups felt that early morning clinics 0800hrs were better than mid-morning clinics at 1100hrs as they get to see and do more procedures. 66%-82% students in both groups felt that the practical training in the OT, ICU and skills lab were very helpful or extremely helpful. The most important aspect of Anesthesiology rotation was "learning basic life saving skills and simulation based learning" according to 85% students in both groups. Nearly 80% students in both groups felt that the training in Anesthesiology should be allotted more time and more weightage in undergraduate training. 72% students in 6th term and 63% students in 8th term felt more confident of handling emergencies after their Anesthesiology rotation. Conclusion: The new curriculum was extremely well received by the students of both groups. The model used for 6th term students comprising of teaching theory and practical in the same term and having early morning clinics, was found to be superior as compared to the model used to teach 8th term students where there was a gap of one year between theory and practical teaching and the clinics were held midmorning.